Analisis Kontekstual mengenai Fungsi Hadis sebagai Pedoman Etika Sosial di Era Digital - Wauran, Meissara Putri Andannari; Anshory, Muhammad Isa (Lembaga Yasin AlSys, 2025)
The digital era has introduced new challenges in social interaction, necessitating ethical guidelines that are both relevant and applicable. This study aims to contextually analyze the function of hadith as a guide for social ethics in navigating digital transformation. A descriptive qualitative method was employed using a literature review approach, focusing on hadiths related to social ethics and their relevance within digital life contexts. The findings show that ethical values found in hadith—such as honesty, respectful speech, preservation of dignity, and mutual respect—remain relevant and can be applied to regulate behavior on social media and other digital platforms. Hadith functions not only as a source of moral norms in Islam but also contains universal principles adaptable to changing times. The study concludes that a contextual understanding of hadith is essential for addressing evolving social dynamics in the digital age. These findings highlight the importance of digital literacy grounded in hadith-based values as a foundation for cultivating civilized, wise, and responsible social ethics in digital spaces.